Changes in Nature of Prediction in Speech Acts: An Experimental Study - V. A. Pishchalnikova; N. I. Stepykin (Научный диалог, 2025)
This article aligns with cognitive and psycholinguistic research on speech acts as indicators of the development of various cognitive processes, a measure of an individual’s linguistic competence, and the extent to which a person masters speech operations. The study investigates changes in the nature of speech acts, reflected in the characteristics of predication (association) between stimuli and responses. Utilizing three associative dictionaries published in different years, the dynamics of prediction in speech acts are demonstrated through the method of interpreting associative fields. The novelty of the research findings lies in substantiating several propositions. In examining the dynamics of speech act execution, the authors emphasize the need to consider different methods of collecting associates: oral-written and written. It is noted that in contemporary linguistic culture, the operations of semantic and surface syntactic processing in speech act production are increasingly supplanted by meaning-based syntactic processing during specific time periods. Indicators of this process include a quantitative increase in topic-comment structures, syntactic primitives, a reduction in the proportion of complete cycle syntactic speech acts, deactivation of surface syntactic processing, a decline in diversity indices within the core of complete cycle syntactic speech acts, and the stereotypization of core associates.